Structure-Activity Relationship for the Oxadiazole Class of Antibacterials - Boudreau, Marc A. (2020)
A structure-activity relationship (SAR) for the oxadiazole class of antibacterials was evaluated by syntheses of 72 analogs and determination of the minimal-inhibitory concentrations (MICs) against the ESKAPE panel of bacteria. Selected compounds were further evaluated for in vitro toxicity, plasma protein binding, pharmacokinetics (PK), and a mouse model of methicillin-resistant Staphylococcus aureus (MRSA) infection. Oxadiazole 72c shows potent in vitro antibacterial activity, exhibits low clearance, a high volume of distribution, and 41% oral bioavailability, and shows efficacy in mouse models of MRSA infection.